Pesquisa de satisfação: um modelo em ouvidorias públicas - ALMEIDA, Nilson Braga de (2023)
Public Ombudsman Offices have been evaluating the provision of their services through satisfaction surveys applied to their users, which do not follow a model. This dissertation aims to propose a reference model of satisfaction survey suitable for adoption in Brazilian Public Ombudsmen. Questionnaires were applied to the independent bodies of the three powers and other instances, operating nationwide, in order to identify characteristics of the satisfaction surveys adopted by their Ombudsman. The collected data were tabulated in a spreadsheet and then subjected to detailed analysis, in which convergences and divergences were identified, as well as recurrent aspects and exceptions regarding the information provided. The results were organized and confronted with the existing theory in the areas that underlie the present study. The technical product was built, whose structure has two main parts: one with general recommendations regarding the application of the satisfaction survey and its results; and another that presents the model developed as a reference in satisfaction surveys for Ombudsmen, containing two closed questions and one open question.